SELF-REGULATED LEARNING SISWA DALAM PEMBELAJARAN MATEMATIKA - anim, Anim; Sirait , Syahriani; Rahmadani, Elfira; Syafitri, Ely (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2023)
This research aims to describe students' self-regulated learning in mathematics learning. The research was conducted using a qualitative-descriptive approach. The research subjects were 30 2nd grade students at State Elementary School No. 010246 Banjar. Data collection was carried out by administering questionnaires and interviews. The research results show that the average questionnaire result for nine SRL indicators is 70.33, which is included in good criteria. The lowest results are found in the indicator